Pemanfaatan Wakaf Tanah untuk Pembangunan Infrastruktur di Bengkulu - Ayu, Devi; Halimatusyadiah, Halimatusyadiah (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Financing is an important factor in empowering waqf land to become productive waqf. Waqf is an innovation to empower waqf assets to make them productive. Bengkulu is one of the regions that has extensive waqf, but its management is not yet optimal. The potential for waqf in Bengkulu is very large and from a number of waqfs which are generally used for mosques, prayer rooms, Islamic boarding schools, madrasas, cemeteries and social services. The management pattern is still traditional and not yet productive. The ability of the waqf nadzir is also the reason why the management pattern is still traditional. The method used in this research is a qualitative approach to literature study with descriptive methods. The data used is primary data and secondary data. The results of this research are the lack of productivity of waqf land in Bengkulu, the obstacles that occur in less productive land waqf and solutions to the obstacles that occur in Bengkulu.